El último dios la lección del siglo XX : un diálogo filosófico con Riccardo Dottori - Gadamer, Hans-Georg, 1900-2002.; Dottori, Riccardo; Iturrate Vea, José Luis (Rubí, Barcelona : Anthropos, Editorial ; México : Universidad Autónoma. Unidad Cuajimalpa, 2009)
"A philosophical and historical testament to the twentieth century, this volume consists of a wide-ranging series of interviews conducted in 1999/2000 between the then centenarian and his former assistant and associate of over thirty years, Riccardo Dottori. These ten dialogues distill and situate Gadamer's philosophy in the context of what has arguably been the bloodiest century in human history. In the course of the interviews, Gadamer addresses - often critically - the work of a wide variety of philosophers, including Heidegger, Nietzsche, Jaspers, Popper, Vico, Habermas, Rorty, and Derrida. He also elaborates on German philosophy during the Nazi period; and, in one of the more fascinating conversations, we are treated to a glimpse of Gadamer's personal perspective on the question of Heidegger's Nazism, including a discussion of the political influence that great philosopher's wife, Elfirde, had on him that tends to contradict most other published accounts. With the possible exception of his autobiography (1985), A Century of Philosophy is perhaps the most accessible expression of Gadamer's life and work in English today." (From the English Ed.)
Introducción / Riccardo Dottori -- 1. Phronesis: una filosofía de la finitud -- 2. ¿Ética o metafísica? -- 3. Utilitarismo, pragmatismo, pluralismo (Calogero, Rorty, Popper) -- 4. Ética y retórica (Vico, Nietzsche, Derrida) 61 -- 5. Metafísica y trascendencia -- 6. Ética y política (Habermas) -- 7. Tradición y emancipación -- 8. La filosofía en medio de la tempestad -- 9. Entre Heidegger y Jaspers -- 10. Hacia una nueva religiosidad -- Apéndice : Un diálogo socrático-- Bibliografía de Hans-Georg Gadamer / José Luis Iturrate Vea -- Índice de nombres
Translation of: L'ultimo dio : un dialogo filosofico con Riccardo Dottori .Roma : Meltemi, 2002.
Includes introduction by R. Dottori (p. 7-22), appendix with one writing by H.G. Gadamer (p. 153-160) and bibliography (p. 163-168).
This work also published in German (Lektion des Jahrhunderts. Münster : Lit, 2002) and English (A century of philosophy. New York : Continuum, 2003)
Includes bibliographical references (p. 163-168).
Keywords: Gadamer, Hans-Georg, -- 1900-2002 -- Interviews; Philosophers -- Germany -- Interviews; Philosophy, Modern -- 20th century; Electronic books